2013
DOI: 10.3390/bs3040536
|View full text |Cite
|
Sign up to set email alerts
|

Functional Perspectives on Emotion, Behavior, and Cognition

Abstract: This Editorial reviews the challenges and advantages posed by a functional perspective on the relationships among emotion, behavior, and cognition. We identify the core themes among the articles published as part of this Special Issue. The articles generally address two important questions: (1) are emotions functional and what is their impact on behavioral and cognitive processes, and (2) how do the interactions among emotion, cognition, and behavior play out in particular situations that present adaptive chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…This three-component conceptualization is consistent with the affect-behavior-cognition model, which illustrates the fundamental facets of social experience (McGuire, 1969;Breckler, 1984;Lewis and Weigert, 1985). It has long been acknowledged that emotion, behavior and cognition present the core interpsychic processes in humans (Lench et al, 2013). Among them, affect refers to emotional bonds, manifested by feelings or mood; cognition consists of knowledge, perceptual responses and thoughts; behavior pertains to overt actions.…”
Section: Dimensions Of Boundary Spanner Closeness To Partner Firmsupporting
confidence: 68%
“…This three-component conceptualization is consistent with the affect-behavior-cognition model, which illustrates the fundamental facets of social experience (McGuire, 1969;Breckler, 1984;Lewis and Weigert, 1985). It has long been acknowledged that emotion, behavior and cognition present the core interpsychic processes in humans (Lench et al, 2013). Among them, affect refers to emotional bonds, manifested by feelings or mood; cognition consists of knowledge, perceptual responses and thoughts; behavior pertains to overt actions.…”
Section: Dimensions Of Boundary Spanner Closeness To Partner Firmsupporting
confidence: 68%
“…Functional perspectives have established that the interplay between emotions, thoughts, and behaviors have evolved to meet environmental demands (Lench et al, 2013). Evidence from this perspective showed that emotional processes play a role in executive functioning tasks, such as future planning (Sass et al, 2013).…”
Section: Ei Optimism and Pessimism In Adolescencementioning
confidence: 99%
“…We also included the three categories that have been shown to be relevant to emotions other than those under investigation, but did not have specific hypotheses for these categories (Lench, Bench, Darbor, & Moore, 2015;Lench, Darbor, & Berg, 2013;Lench et al, 2011).…”
Section: The Language Of Positive Emotionsmentioning
confidence: 99%